Maternal microplastic exposure during pregnancy and risk of gestational diabetes mellitus associated with gut dysbiosis - Deboral Panneerselvam; Anuradha Murugesan (Medicine in Microecology, 2023)
The increased production and consumption of plastic items in the modern era has resulted in the generation of numerous microplastics (MPs) in the environment. Numerous researchers and clinicians were intrigued by the world's extensive use, distribution, and abundance of MPs. They were curious to study their interactions with biological systems and their impact on human health. Microplastic exposure occurs through various routes like oral, dermal, and inhalation, leading to metabolism alteration, oxidative stress, neurotoxicity, reproductive toxicity, and carcinogenicity. Microplastics contain intentionally added additives that, when combined, act as endocrine disruptors (EDCs), disrupting the natural hormone system and can cause cancer, diabetes, and neurological impairment in a developing fetus. The EDCs in microplastics may regulate glucose homeostasis, as shown by the occurrence of gestational impaired glucose tolerance, leading to Gestational Diabetes Mellitus (GDM). As the primary route of exposure to microplastics in humans is through ingestion, microplastics, and their additives ultimately enter the gastrointestinal tract and alter the gut microflora. Numerous metagenomics studies have demonstrated that the gut microflora of women with GDM are enriched with organisms like Ruminococcae, Parabacteroides distansonis, and Prevatella. The metabolic pathways for insulin signaling and carbohydrate metabolism are connected to these microbiota populations. The impact of microplastics on maternal exposure and their possible alteration of glucose metabolism, leading to GDM, as well as their association with gut microbiome dysbiosis, are addressed in this review.